Corpo e cultura: culto ao corpo e vigorexia - Serem Junior, Vanderley Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Currently the company suffers a heavy influence of media, through their tentacles people are reached and clawed into a consumerist context, and the reason for the success of this market share is linked to aesthetics. An ideal beauty standard is followed, aimed at recognizing social, emotional success, professional and loving. Thus, people are accustomed from his childhood with the image of a perfect prince or princess, heroes that is becoming increasingly more muscular and developed throughout the evolution of cinema. While the aesthetic perfection is internalized by society and see that this beauty is not a particular good for some people, but everyone should become pretty standard to suit hence those who do not fit this stereotype are somehow excluded from the circle of society standard. One way people try to develop and hone the look is through weight training exercises in specialized academies. The problem is when it appears not the contentment of the individual in relation to his body. Even when your muscles are increasing, for the person who suffers from Vigorexia changes are significant to the point never to be content with their state of development, which is seen distorted and underestimated. Thus this paper aims to describe the situation and how the routine Vigorexia context and people are distorted to suit the aesthetic and social demands that are made, through a literature search on the muscle dysmorphia. It is of paramount importance to know the pathological picture of Vigorexia not only by professionals of Psychology, Psychiatry and Medicine, but also for Physical Educators that are constantly present in an active and that can positively or negatively influence the routine and pathological picture of these people with Muscular Dysmorphia

Atualmente a sociedade sofre uma pesada influência da Mídia, através de seus “tentáculos” as pessoas são alcançadas e agarradas para dentro de um contexto consumista, e a razão do sucesso dessa fatia de mercado está ligado à estética. Um padrão de beleza ideal é seguido, visando o reconhecimento social, sucesso afetivo, profissional e amoroso. Desta forma, as pessoas desde sua infância estão acostumadas com a imagem de um príncipe ou princesa perfeitos, de heróis que vem se tornando cada vez mais musculosos e desenvolvidos ao longo da evolução do cinema. Ao passo que a perfeição estética é interiorizada pela sociedade e esta vê que a beleza não é um bem particular de algumas pessoas, mas sim, todos devem se tornar belos para se adequarem ao padrão, consequentemente, os que não se adéquam a esse estereotipo estão de alguma forma excluídos do círculo da sociedade “padrão”. Uma forma das pessoas tentarem desenvolver e lapidar a aparência é através de exercícios de musculação, em academias especializadas. O problema está quando aparece o não contentamento do indivíduo em relação ao seu corpo. Mesmo quando seus músculos estam se hipertrofiando, para a pessoa que sofre de Vigorexia as mudanças nunca são significativas ao ponto de se contentar com seu estado de desenvolvimento, que é visto de forma distorcida e subestimado. Assim este trabalho procura descrever a situação da Vigorexia e como a rotina e o contexto das pessoas são distorcidos para se adequar as exigências estéticas e sociais que são feitas; por meio de uma pesquisa bibliográfica sobre à dismorfia muscular. É de suma importância conhecer o quadro patológico da Vigorexia, não só por profissionais da Psicologia, Psiquiatria e Medicina, mas sim também por Educadores Físicos que constantemente estão presentes de forma ativa e que pode influenciar positiva ou negativamente...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Linguagem corporal; Imagem corporal; Estética; Vigorexia; Musculos - Dimorfismo; Imagem corporal - Aspectos psicológicos